Intracranial Serpentine Aneurysms: Spontaneous Changes of Angiographic Filling Pattern - Kandemirli, S.G.; Cekirge, S.; Oran, I.; Saatci, I.; Kizilkilic, O.; Cinar, C.; Islak, C.; Kocer, N. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Serpentine aneurysms are partially thrombosed aneurysms with an eccentrically located tortuous intra-aneurysmal vascular channel. The large size, distinctive neck anatomy, and supply of the brain parenchyma by the outflow tract pose technical challenges in treatment. The aim of this study was to discuss the endovascular treatment results and illustrate the dynamic nature of serpentine aneurysms. Spontaneous transformation of saccular and fusiform aneurysms into serpentine morphology, along with a case of serpentine-into-fusiform aneurysm transformation during follow-up, is presented.MATERIALS AND METHODS: A retrospective analysis from 3 institutions revealed 15 patients with serpentine aneurysms who underwent diagnostic evaluation and endovascular treatment. Nine of the 15 patients underwent endovascular occlusion of the parent vessel with detachable balloon or coils. Six of the 15 patients underwent aneurysm and parent artery occlusion with coiling.RESULTS: In 11 patients, improvement or resolution of symptoms was achieved by an endovascular approach without any treatment-related morbidity. Morbidity related to treatment in the immediate postoperative period was seen in 3 patients, with resolution of the deficits at long-term follow-up in 2 patients and persistence of a mild deficit in 1 patient. Endovascular treatment failed to achieve resolution of symptoms in a case with a basilar tip aneurysm treated by aneurysm coiling.CONCLUSIONS: Serpentine aneurysms are dynamic structures with spontaneous transformation possible from a saccular or fusiform shape into a serpentine configuration. An endovascular approach by parent vessel occlusion or intra-aneurysmal occlusion is a successful treatment technique for serpentine aneurysms.ACAanterior cerebral arteryBTOballoon test occlusionECAexternal carotid arteryPAOparent artery occlusionPCAposterior cerebral artery